In Silico Evaluation of Indole-3-Carbinol from Kale (Brassica oleracea L.) Against Cervical Cancer Through IGF2BP2 and MYCBP Targeting - Farhan Abdullah Rizal; Humairah Medina Liza Lubis (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Cervical cancer remains one of the leading causes of morbidity and mortality worldwide, including in Indonesia, involving metabolic reprogramming such as the Warburg effect in tumorigenesis. The proteins IGF2BP2 and MYCBP are known to play important roles in promoting cancer cell proliferation through the regulation of cellular metabolism. Objective: This study aimed to investigate the anticancer potential of Indole-3-Carbinol against cervical cancer by targeting IGF2BP2 and MYCBP using an in silico approach. Method: The study employed molecular docking analysis targeting IGF2BP2 and MYCBP proteins, using 5-fluorouracil and doxorubicin as comparator compounds. Result: The results showed that Indole-3-Carbinol exhibited binding energy (∆G) values of -3.20 kcal/mol for IGF2BP2 and -5.75 kcal/mol for MYCBP, with better binding affinity than 5-fluorouracil but lower than doxorubicin. Interaction analysis revealed that Indole-3-Carbinol interacted with both IGF2BP2 and MYCBP proteins, with IGF2BP2 showing a higher number of interacting amino acid residues. Further studies are required to confirm its preferential molecular target. Furthermore, Indole-3-Carbinol fulfilled Lipinski’s criteria, demonstrated high gastrointestinal absorption, the ability to penetrate the blood-brain barrier, and a favorable toxicity profile without carcinogenic effects. Conclusion: Indole-3-Carbinol shows preliminary in silico potential as a cervical anticancer candidate targeting the IGF2BP2 pathway and modulating the Warburg effect, with the advantage of being a relatively safe natural compound.